Mirror modes in the Earth's magnetosheath: Results from a global hybrid‐Vlasov simulation. Issue 5 (12th May 2016) - Hoilijoki, Sanni; Palmroth, Minna; Walsh, Brian M.; Pfau‐Kempf, Yann; von Alfthan, Sebastian; Ganse, Urs; Hannuksela, Otto; Vainio, Rami
Abstract: We investigate mirror mode structures in the Earth's magnetosheath using our global kinetic Vlasiator simulation, which models ion behavior through their distribution function and treats electrons as a charge‐neutralizing fluid. We follow the evolution of waves as they advect along velocity streamlines through the magnetosheath. We find that mirror mode waves are observed preferentially in the quasi‐perpendicular magnetosheath along velocity streamlines that enter the sheath in the vicinity of the foreshock ULF wave boundary where there are enough initial perturbations in the plasma for the mirror modes to grow, and the plasma properties fulfill the mirror instability condition better than elsewhere in the magnetosheath. We test selection criteria defined by previous studies and show that the spatial extent over which mirror modes occur ranges from much of the magnetosheath on the quasi‐perpendicular side of the subsolar point to very small isolated regions depending on the criteria. Key Points: We observe mirror mode waves in quasi‐perpendicular magnetosheath in global hybrid‐Vlasov simulation Most activities are observed along streamlines entering the sheath near foreshock ULF wave boundary The area of the sheath showing mirror mode activity is highly dependent on the selection criteria